Correction to: Expression of factors involved in apoptosis and cell survival is correlated with enzymes synthesizing lysophosphatidic acid and its receptors in granulosa cells originating from different types of bovine ovarian follicles - Emilia Sinderewicz; Katarzyna Grycmacher; Dorota Boruszewska; Ilona Kowalczyk-Zięba; Joanna Staszkiewicz; Tomasz Ślężak; Izabela Woclawek-Potocka (BMC, 2017)
Correction After publication of the original article [1] it was noted that the caption of Table two was incorrect. This caption should read "Distribution of ovarian follicles depending on the type (healthy, transitional, and atretic) Small superscript letters a and b indicate significant differences in the respective ovarian follicle numbers within thevarious types of follicles (P < 0.05) as determined by a one-way ANOVA followed by the Kruskall-Wallis test.".